Low threshold characteristics of an L-band Brillouin-erbium comb fiber laser in a linear cavity - Al-Mansoori, Mohammed Hayder; Iqbal, Syed J.; Abdullah, Mohd. K.; Mahdi, Mohd. A. (OSA Publishing, 2006)
The L-band linear-cavity multiwavelength Brillouin-erbium fiber laser source has been experimentally investigated. The proposed L-band laser cavity exhibits a low threshold power of similar to 23.4 mW due to the high efficiency of double-pass amplification in the erbium gain medium and also bidirectional generation of the Brillouin pump in the single-mode fiber. The effects of Brillouin pump power and the wavelength on the threshold pump power are also discussed. Consequently, it has been found that there is a limited range for the Brillouin pump wavelength to achieve a lasing condition in the laser cavity. (c) 2006 Optical Society of America.